TET2 regulates osteoclastogenesis by modulating autophagy in OVX-induced bone loss. Issue 12 (2nd December 2022) - Yang, Chen; Tao, Huaqiang; Zhang, Haifeng; Xia, Yu; Bai, Jiaxiang; Ge, Gaoran; Li, Wenming; Zhang, Wei; Xiao, Long; Xu, Yaozeng; Wang, Zhirong; Gu, Ye; et al.
ABSTRACT: Increased bone resorption by osteoclasts after estrogen deficiency is the main cause of postmenopausal osteoporosis. TET2 (tet methylcytosine dioxygenase 2) is a DNA demethylase that regulates cellular function and differentiation potential. Macroautophagy/autophagy maintains cellular homeostasis by recycling unnecessary and damaged organelles. This study revealed that TET2 promoted bone loss in oophorectomized (OVX) mice and that TET2 promoted osteoclast differentiation by regulating autophagy. Tet2 knockdown inhibited autophagy and osteoclast differentiation in vitro. Mechanistically, Tet2 knockdown increased BCL2 (B cell leukemia/lymphoma 2) expression and BCL2 exhibited increased binding to BECN1 and negatively regulated autophagy. Small interfering RNA specific to Bcl2 interfered with BCL2 expression in Tet2 -knockdown bone marrow cells/precursors, partially reversing autophagy dysregulation and promoting osteoclast differentiation. Moreover, the LV-sh Tet2 lentivirus prevented bone loss in OVX mice. In summary, our findings provide evidence that TET2 promotes osteoclast differentiation by inhibiting BCL2 expression and positively regulating BECN1-dependent autophagy. Abbreviations : ACP5/TRAP: acid phosphatase 5, tartrate resistant; ATP6V0D2: ATPase, H+ transporting, lysosomal V0 subunit D2; BCL2: B cell leukemia/lymphoma 2; BECN1: beclin 1, autophagy related; BMs: bone marrow cells; CTSK: cathepsin K; MAP1LC3B/LC3B: microtubule-associated protein 1 light chain 3 beta; MMP9: matrix metallopeptidase 9; OVX: oophorectomy; RUNX1: runt related transcription factor 1; SOCS3: suppressor of cytokine signaling 3; SPI1/PU.1: Spi-1 proto-oncogene; TNFSF11/RANKL: tumor necrosis factor (ligand) superfamily, member 11; TET2: tet methylcytosine dioxygenase 2.